Primary open-angle glaucoma: on the development of novel therapeutic approaches - CROSBIE, DARRAGH (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2018)
Glaucoma is one of the most prevalent forms of preventable blindness, affecting more than 60 million people worldwide. While normotensive forms of the disease do exist, the majority of cases are caused by elevations in intraocular pressure. The open-angle form of the disease is the most common and the primary standard of care is the use of topically-applied pressure reducing medications. Such medications work either by slowing down the production of aqueous humour, or increasing its outflow from the eye. Interestingly, none of these medications target the major route of aqueous humour outflow, the conventional outflow pathway, comprised of the trabecular meshwork and Schlemm?s canal. Current therapies often fail to meet adequate IOP reduction and surgical intervention is required in these cases, which can result in significant side effects. There is, therefore, a distinct unmet clinical need for therapies primarily targeting the conventional outflow pathway and the work presented in this thesis directly addresses this issue using the mouse as an animal model. Chapter 2 (after the general introduction of Chapter 1) describes work in which tight junction components joining the endothelial cells lining Schlemm?s canal were identified in in vitro and in vivo studies in human, primate and mouse, with a view to then down-regulating these via siRNA delivery to the mouse AC (results of overall project reported in Tam et al., (2017). Furthermore, a similar approach was used down-regulate claudin-5 and occludin tight junction proteins in endothelial cells of the inner retina in the DBA/2J glaucoma mouse, resulting in increased clearance of soluble amyloid-β (1-40) from the ganglion cell layer. In Chapter 3, an entirely different approach was addressed, the objective being to identify an AAV pseudotype capable of efficiently transducing tissues of the conventional pathway for therapy delivery. While (contrary to other reports) none of the 6 strains of AAV transfected the outflow tissues, AAV2/9 was shown to extensively transduce the corneal endothelium, offering a platform for delivery of soluble compounds to the eye. As part of a group effort, this virus was further used to deliver MMP-3 to the outflow pathway, enhancing aqueous humour outflow, as reported in O?Callaghan, Crosbie, et al. (2017). In addition, the effects of plasminogen activator inhibitor-1 (PAI-1) on the tissues of the conventional outflow pathway were investigated. PAI-1 increased extracellular matrix deposition and cell contractility of these cells in vitro. Its effect, in vivo, was evaluated using the AAV2/9 system, with the hope of creating a mouse model system for experimental modulation of aqueous outflow. However, no elevations in IOP or reductions in outflow facility were observed, which may have been due to insufficient PAI-1 secretion. Chapter 4 reports data on the use of MRI in assessment of the mouse eye. Assessment of aqueous humour flow dynamics in a model is important in novel treatment discovery. Age-related changes in aqueous humour dynamics, morphology and blood-aqueous barrier integrity were detected in the DBA/2J pigmentary glaucoma mouse model. Use of MRI in this scenario is in its infancy, and the results obtained clearly indicate a great potential for the use of this technique in glaucoma research. Hopefully, these approaches will be of use in development of clinical therapies for glaucoma.
APPROVED
Keywords: PAI-1; AAV; MRI; Tight Junctions; Claudin; Schlemm's canal; Trabecular Meshwork; Eye; Ocular disease; Glaucoma; Viral therapy